Clinical trials in health-care metaverse – A conceptual overview - J. Mohammed Sulaiman Sait; S. Sarumathy (Perspectives in Clinical Research)
Post-COVID-19, the emergence of newer technologies has taken center stage. One such technology is metaverse, which is an extension of existing technologies such as virtual reality (VR) and augmented reality (AR) that enables a fully immersive communication platform through the utilization of digital twins and avatars in a three-dimensional digital space. Literature review has shown that the adoption of such technologies in the field of clinical trials can help in improving the therapeutic outcomes in patients while having numerous other benefits. Despite its early stages of adoption, the application of metaverses in clinical trials through the use of AR, VR, and digital twins holds the ability to revolutionize key tasks in clinical trials, such as patient enrollment, engagement, monitoring, and counseling, by removing barriers to study participation. This review article focuses on the concepts of metaverse, its use in clinical trials, its inherent benefits, and limitations and serves as a starting point for clinical research organizations, pharmaceutical companies, and technology firms to conceptualize and develop metaverse solutions that stand to significantly benefit the broader landscape of clinical trials.